KEKAYAAN JENIS TUMBUHAN TAMAN NASIONAL GUNUNG HALIMUN*[Plant Biodiversity Richness of Gunung Halimun National Park] - Wiriadinata, Harry (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Mounts Halimun National Park in West l Java has a very high plant diversity. The plant diversity composes of flowering plants.ferns, mosses and fungi. They are very important in biodiversity as their functions to keep good environments and protect the living endangered creatures such as Javanese eagle, panther, hornbill and gibbon. Data on the plant diversity is important for the park management, education ami ecouirism. Invcntarisation ofplants from many areas within the park will be presented.